The Effect of Using Listen Read Discuss (LRD) Strategy to Improve Students Reading Compehension on Narrative Text at Tenth Grade SMA Negeri 5 Bungo - Rosa Melia; Dodi Widia Nanda; Riyadi Saputra (The Future of Education Journal, 2022)
The aimed of this study was to determine the effect of using Listen Read Discuss (LRD) strategy to improve students reading comprehension on narrative text at tenth grade SMA Negeri 5 Bungo. There were some problems in this research. First, the students lack of vocabulary. Second, the students lack motivated to read. Third, the students difficult to get main idea in reading comprehension.The population of this research were 88 students. The sampling technique in this research used purposive sampling. The sample of this research X IPA 1 as the experimental class consists of 29 students, and X IPA 2 as the control class consists of 29 students. This research used a quasi-experimental design. The data collection technique was taken by giving pre-test and post-test in the form of a multiple choice of 20 questions. Data analysis techniques to improve students reading comprehension used descriptive statistics, normality test and homogeneity test, hypothesis test with independent sample t-test, and N-Gain scores.The results of the independent sample t-test showed that the significance level was 0.000 < 0.05. The mean score of N-Gain for experimental class is 0.52 included in the medium category and the mean score of N-Gain for the control class is 0.19 included in the low category. It means that Ha was accepted while Ho was rejected. It be concluded the Listen Read Discuss (LRD) strategy was effective to improve students reading comprehension on narrative text at tenth grade SMA Negeri 5 Bungo.